Utilization of Livestock Waste Into Organic Fertilizer in Haurngombong Village, Pamulihan District, Sumedang Regency - Maulana, Yasin Pradana; Hidayati, Yuli Astuti; Marlina, Eulis Tanti; Harlia, Ellin; Badruzaman, Deden Zamzam (Unpad Press, 2025)
The utilization of livestock waste as organic fertilizer is a strategic effort to address waste problems in rural areas and to support sustainable agriculture. This community service activity was conducted in Haurngombong Village, Pamulihan District, Sumedang Regency. The objective of this activity was to improve the knowledge and skills of the community in processing livestock waste into high-quality solid and liquid organic fertilizers. The methods used included counseling, interactive discussions, and direct demonstration of waste processing techniques. The results showed a significant improvement in participants' understanding, as evidenced by the increased post-test scores. The community responded enthusiastically and committed to adopting the introduced technologies for sustainable waste management.